ASSESSMENT OF AWARENESS LEVELS ON GOAT MILK AND PRODUCTS: THE CASE OF ÇANAKKALE - Ferhan SAVRAN; Özdal KÖKSAL; Duygu AKTÜRK; Sema GÜN; Gülçin KAYA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Cheese production from goat milk has a core place in Çanakkale’s economy. The present study was conducted to determine the consumption trends in goat milk and products and to determine the factors effective in preference of these products. Data were gathered from the household through questionnaires.